2010
DOI: 10.1037/a0019376
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of parenting behaviors and perceived discrimination predicting Latino adolescents' ethnic identity.

Abstract: Characteristics of the familial and societal context were examined as predictors of Latino adolescents' (N ϭ 323; 49.5% female) ethnic identity. Consistent with previous work, familial ethnic socialization significantly predicted future levels of ethnic identity exploration, resolution, and affirmation for both male adolescents and female adolescents, although the association was significantly stronger for female adolescents than male adolescents for exploration and resolution. Furthermore, for male adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
141
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 85 publications
15
141
3
Order By: Relevance
“…For example, Umana-Taylor and Guimond (2010) found that Latino adolescents' reports of perceived ethnic socialization significantly predicted their subse quent ethnic identity exploration and resolution or commitment across the high school years. Because ethnic socialization practices emphasize the experience of ethnic minority status and aim to pass down one's cultural heritage, traditions, and customs to children, they serve the purpose of fostering ethnic identity development in adolescents and perpetuating one's culture in future generations.…”
Section: Ethnic Socializationmentioning
confidence: 96%
“…For example, Umana-Taylor and Guimond (2010) found that Latino adolescents' reports of perceived ethnic socialization significantly predicted their subse quent ethnic identity exploration and resolution or commitment across the high school years. Because ethnic socialization practices emphasize the experience of ethnic minority status and aim to pass down one's cultural heritage, traditions, and customs to children, they serve the purpose of fostering ethnic identity development in adolescents and perpetuating one's culture in future generations.…”
Section: Ethnic Socializationmentioning
confidence: 96%
“…In further support of this proposition, Romero and Roberts (1998) and Umaña- Taylor and Updegraff (2006) found that perceived discrimination was associated with ethnic identity affirmation and ethnic identity exploration, such that increases in perceived discrimination were associated with increases in both ethnic identity affirmation and ethnic identity exploration. Umaña- Taylor and Guimond (2012) similarly found that discrimination was associated with ethnic identity exploration, affirmation, and resolution over time, although they observed some cross-gender differences. For females, increases in discrimination were associated with increased exploration and resolution, but decreased affirmation.…”
Section: Acculturationmentioning
confidence: 97%
“…One such set of parenting practices is ethnic-racial socialization, or socialization practices transmitting information regarding race and ethnicity to children (Hughes et al, 2006). Evidence indicates that ethnic-racial socialization is associated with a range of positive outcomes for ethnic minority children, primarily in the domains of ethnic identity development and other psychosocial outcomes (Bennett, 2006; Burt, Simons, & Gibbons, 2012; Caughy, O’Campo, Randolph, & Nickerson, 2002; Hughes, Hagelskamp, Way, & Foust, 2009; Neblett, Banks, Cooper, & Smalls-Glover, 2013; Rodriguez, Umaña-Taylor, Smith, & Johnson, 2009; Umaña-Taylor & Guimond, 2010). Hughes et al (2006) delineated four types of ethnic-racial socialization: cultural socialization, preparation for bias, promotion of mistrust, and egalitarianism/silence about race.…”
mentioning
confidence: 99%